2018
DOI: 10.1371/journal.ppat.1007445
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome screen reveals a novel relationship between Wolbachia levels and Drosophila host translation

Abstract: Wolbachia is an intracellular bacterium that infects a remarkable range of insect hosts. Insects such as mosquitos act as vectors for many devastating human viruses such as Dengue, West Nile, and Zika. Remarkably, Wolbachia infection provides insect hosts with resistance to many arboviruses thereby rendering the insects ineffective as vectors. To utilize Wolbachia effectively as a tool against vector-borne viruses a better understanding of the host-Wolbachia relationship is needed. To investigate Wolbachia-ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 88 publications
(99 reference statements)
4
47
0
Order By: Relevance
“…A recent cell-based genome-wide RNAi screen in D. melanogaster cells infected with the wMel strain of Wolbachia found that bacterial density, or titer, increases when host ribosomal and translation initiation proteins are knocked down. This suggests that Wolbachia interacts with some of these factors in wild-type cells to alter host translation (Grobler et al 2018). This is fascinating given the trends we reported in the previous section, which found that generally only highly virulent pathogens interfere with host translation.…”
Section: B Other Known Strategies Of Wolbachia-mediated Control Of supporting
confidence: 54%
See 1 more Smart Citation
“…A recent cell-based genome-wide RNAi screen in D. melanogaster cells infected with the wMel strain of Wolbachia found that bacterial density, or titer, increases when host ribosomal and translation initiation proteins are knocked down. This suggests that Wolbachia interacts with some of these factors in wild-type cells to alter host translation (Grobler et al 2018). This is fascinating given the trends we reported in the previous section, which found that generally only highly virulent pathogens interfere with host translation.…”
Section: B Other Known Strategies Of Wolbachia-mediated Control Of supporting
confidence: 54%
“…This is fascinating given the trends we reported in the previous section, which found that generally only highly virulent pathogens interfere with host translation. Supporting a role for translation interference in Wolbachia nutrition, this (Grobler et al 2018) and another cell screen (White et al 2017), found that Wolbachia titer decreased when host ubiquitination was inhibited. Furthermore, White et al (2017) found that Wolbachia infection significantly increases ubiquitination levels in the host cell.…”
Section: B Other Known Strategies Of Wolbachia-mediated Control Of mentioning
confidence: 84%
“…This reliance on host processes has led to the link of many metabolic pathways as essential in regulating Wolbachia density within the host. Despite the initial belief that consumption of host amino acids by Wolbachia was via ERAD-driven proteolysis [ 84 ], recent work suggests that amino acids are obtained from the core proteasome by bacteria strategically positioned between the ER and the Golgi [ 109 , 110 ]. This is only one of many ways by which Wolbachia seems to be interacting with host metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…B). This is in accordance with previous studies indicating that hosts infected with Wolbachia exhibit high levels of proteasome activity to support maintenance of Wolbachia for optimal survival (Fallon & Witthuhn, ; White et al ., ; Grobler et al ., ), such as Wolbachia competing with its host for amino acids (Caragata et al ., ).…”
Section: Discussionmentioning
confidence: 99%